IMPLEMENTASI PENGGUNAAN AI SEBAGAI MEDIA PENDIDIKAN AGAMA ISLAM DI SD N BAGELEN - Muhammad Abdul Malik; Nur Rohmah Hayati (Institut Agama Islam Negeri Pontianak, 2025)
This study explores the use of Artificial Intelligence (AI) as a learning medium in Islamic Religious Education (IRE) at SD Negeri Bagelen. The research stems from the increasing demand for adaptive and interactive learning in the 21st century, while the integration of AI in Islamic education remains limited. A qualitative case study approach was employed with subjects including Islamic Education teachers, fourth to sixth grade students, and the school principal. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings reveal that AI has great potential to enhance the effectiveness of Islamic education by facilitating personalized learning, providing instant feedback, and creating engaging experiences through chatbots, virtual tutors, and gamification. However, implementation at SD N Bagelen still faces significant challenges, such as limited digital infrastructure, low teacher digital literacy, and the absence of curriculum guidelines for AI integration in religious education. In conclusion, AI utilization in Islamic education can improve students’ motivation and learning outcomes, but requires integrative strategies, including teacher capacity building, technology-based curriculum development aligned with Islamic values, and collaboration among stakeholders.